2021
DOI: 10.7759/cureus.13470
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors and Lung Cancer: History, Epidemiology, and Market Outlook

Abstract: Lung cancer is a leading cause of death for both men and women. The treatment of lung cancer has been stifled with pessimism for many years. However, molecularly targeted therapies directed at pathologic epidermal growth factor receptor tyrosine kinases have come to market and, with them, a new tone to an old diagnosis. Treatment of lung cancer is a complex science that requires not only anatomical knowledge of the patient but also an understanding of the patient's overall physiologic condition. When patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Of note, in our study, 26 patients (13.5% of those tested) had tumors harboring the T790M mutation in the same tissue sample used for EGFR mutation analysis; despite a very few amount of mutated alleles being detected by NGS assay, such a subset of patients presented a consistently worse prognosis in comparison with cases who did not had the T790M variant. The EGFR-T790M mutation alone accounts for up to 50% of resistances in TKIs, which affect the majority of patients within the first year of treatment, and is considered quite rare at diagnosis, being the main mechanism of acquired (or secondary) drug resistance [ 14 16 ]. In this sense, our data show that, even if such a mutation is present at sub-clonal level in about one tenth of cases at the time of diagnosis, it may somehow affect the tumor behavior by causing intrinsic (or primary) drug resistance and inducing poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in our study, 26 patients (13.5% of those tested) had tumors harboring the T790M mutation in the same tissue sample used for EGFR mutation analysis; despite a very few amount of mutated alleles being detected by NGS assay, such a subset of patients presented a consistently worse prognosis in comparison with cases who did not had the T790M variant. The EGFR-T790M mutation alone accounts for up to 50% of resistances in TKIs, which affect the majority of patients within the first year of treatment, and is considered quite rare at diagnosis, being the main mechanism of acquired (or secondary) drug resistance [ 14 16 ]. In this sense, our data show that, even if such a mutation is present at sub-clonal level in about one tenth of cases at the time of diagnosis, it may somehow affect the tumor behavior by causing intrinsic (or primary) drug resistance and inducing poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with non‐small cell lung cancer (NSCLC) typically present with advanced‐stage disease at diagnosis and have poor prognoses. However, the introduction of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) has revolutionized the management of EGFR ‐mutated advanced NSCLC, and they are currently recommended as the first‐line treatment of choice in several international guidelines 2,3 . Clinical trials and real‐world evidence have shown that EGFR‐TKIs significantly improve progression‐free (PFS) and overall (OS) survival compared to historical standard platinum‐based chemotherapy in patients with EGFR ‐mutated advanced NSCLC 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) has revolutionized the management of EGFR ‐mutated advanced NSCLC, and they are currently recommended as the first‐line treatment of choice in several international guidelines. 2 , 3 Clinical trials and real‐world evidence have shown that EGFR‐TKIs significantly improve progression‐free (PFS) and overall (OS) survival compared to historical standard platinum‐based chemotherapy in patients with EGFR ‐mutated advanced NSCLC. 4 , 5 In addition, previous studies have shown that EGFR‐TKIs significantly reduce the symptomatic burden and improve the quality of life of affected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinoma (LUAD) is the main subtype of NSCLC, accounting for about 60% of all NSCLC cases ( 1 - 3 ). Many potential therapeutic targets and corresponding targeted drugs have been discovered and applied in clinics for the treatment of LUAD, including epidermal growth factor receptor (EGFR), fibroblast growth factor receptor, and insulin-like growth factor ( 4 - 6 ). Nevertheless, there is an urgent need to discover more potential and effective target genes in LUAD to further improve the treatment strategy.…”
Section: Introductionmentioning
confidence: 99%